ANALISIS PENGARUH MOTIVASI, PELATIHAN, DAN INSENTIF KERJA TERHADAP KINERJA KARYAWAN ES TEH INDONESIA DI JAWA TIMUR - Hakim, M. Firman (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2025)
This research aims to analyze the influence of motivation, training, and work incentives on employee performance at Es Teh Indonesia in East Java. The study employs a quantitative approach with a causal relationship design to explain the impact of three independent variables—motivation, training, and work incentives—on employee performance. The total population of 40 employees was selected through a total sampling technique. Data were collected using a structured questionnaire based on Likert scale measurements and processed through multiple linear regression analysis using SPSS version 26. The results indicate that motivation, training, and work incentives have both partial and simultaneous significant effects on employee performance. Among these variables, the training factor demonstrates the strongest influence, confirming that continuous skill development is a key driver of performance improvement in the beverage franchise industry. This finding implies that performance outcomes in Es Teh Indonesia depend not only on monetary rewards or motivation but also on structured competency enhancement through regular and targeted training programs. The study highlights that a well-balanced combination of intrinsic and extrinsic motivators contributes to sustainable productivity and operational excellence in franchise-based organizations.